SHAKESPEREAN APPARATUS: EXPLICIT TEXTUAL STRUCTURES AND THE IMPLICIT NAVIGATION OF ACCUMULATED KNOWLEDGE - Siemens, Raymond (Surfaces, 1999)
In its exploration of the potential for hypertextual navigation offered by the new humanistic understanding of text, the article analyzes a traditional humanistic activity — that of annotating a scholarly edition (in this case, one of Shakespeare’s sonnets). It asserts that the interaction allowed by advanced textual analysis software are transferable to all the material that can be linked to the text. Moreover, semantic patterns, especially those identified with machine facilitation, operate in ways akin to hypertextual links.